Mastering Primary Open Augmentation Rhinoplasty: Techniques, Innovations, and Outcomes - Mohd. Altaf Mir; Jaya Jain (Key Flaps in Plastic Surgery, 2023)
This book chapter discusses the surgical technique of primary open augmentation rhinoplasty, focusing on a case of congenital depressed nasal deformity. The patient presented with a depressed dorsum of the nose and an undefined nasal tip, but normal nasal function. The operative procedure involved creating transcoloumellar and infracartilagineous endonasal incisions, followed by the creation of a subcutaneous pocket. Rib cartilage was harvested, carved, and placed as an L-strut cartilage graft in the subcutaneous pocket. The chapter highlights the satisfactory postoperative results observed during follow-up examinations. The chapter introduces primary open augmentation rhinoplasty as a surgical procedure aimed at enhancing the appearance and structure of the nose by adding volume and improving its shape. It emphasizes the importance of patient evaluation and planning to customize the surgical approach based on the patient’s nasal anatomy and aesthetic goals. The open approach, achieved through specific incisions, allows for direct visibility and precise modifications to the nasal framework. The surgical technique includes the use of cartilage grafts, harvested from various sources, to add volume, improve projection, and refine the nasal tip. The chapter emphasizes the versatility of primary open augmentation rhinoplasty in addressing a wide range of nasal concerns, such as nasal projection, tip refinement, and asymmetry correction. It highlights the advantages of the technique, including precise visualization and control, long-lasting results, and patient satisfaction. However, the chapter also acknowledges the limitations of the procedure, which include the need for surgical expertise, realistic patient expectations, and potential complications such as infection, bleeding, asymmetry, and changes in nasal sensation. The importance of choosing a qualified and experienced plastic surgeon, along with proper patient selection, meticulous surgical technique, and postoperative care, is emphasized to minimize these risks. Overall, the chapter provides valuable insights into the surgical technique and considerations involved in primary open augmentation rhinoplasty, highlighting its potential benefits and limitations for patients seeking nasal enhancement.